1994
DOI: 10.1038/bjc.1994.333
|View full text |Cite
|
Sign up to set email alerts
|

Is an increase in CA 125 in breast cancer patients an indicator of pleural metastases?

Abstract: S_lThe retrospective analysis of 250 breast cancer patients with disseminated disease provided evidence that the increase in CA 125 serum levels in these patients was caused by lung metastases or pleural effusions. Seven patients with lung metastases and pleural involvement had elevated CA 125 levels, while in four patients with lung metastases but without pleural effusions CA 125 levels remained normal. In patients with only bone or liver metastases ResultsOf a group of 250 patients with disseminated breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several investigators reported elevated CA 125 levels to be associated with pleural or pericardial involvement in benign and malignant diseases [13,14]. In this study, 5 of 6 patients with abdominal tumor masses and such serosal involvement had elevated CA 125 concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…Several investigators reported elevated CA 125 levels to be associated with pleural or pericardial involvement in benign and malignant diseases [13,14]. In this study, 5 of 6 patients with abdominal tumor masses and such serosal involvement had elevated CA 125 concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…Other reports [28][29][30] have shown that increased CA 125 is a negative predictor with regard to survival for breast cancer patients, and that it is a sensitive marker for lung and pleural metastases. These reports suggest that the increased CA 125 concentration is caused by pleural metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994 Jager et al [30] published a report describing 26 breast cancer patients with isolated metastases. Seven out of 11 patients with lung metastases had elevated CA 125 concentrations, of which 5 had pleural fluid, while 15 patients with liver or bone metastases had normal CA 125 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, when studying new tumor markers, it is very important to evaluate the specificity, in other words, to know the source of false-positive results [17][18][19]28]. Knowledge of false positives will enable their avoidance and better application may be obtained [21,[29][30][31]. S-100 specificity in benign and malignant conditions other than malignant melanoma has only rarely been studied.…”
Section: Discussionmentioning
confidence: 99%